Kepentingan keperluan keselamatan dalam pembangunan perisian - Kamalrudin, Massila; Yusop, Noorrezam (Penerbit UTeM Press, 2023)
Software engineering students can learn validation of security software requirements in the Industrial Revolution 4.0 Revolution. The book contains seven chapters on security requirements engineering and MobiMEReq in action. This book can be a reference source for software engineering students and industry practitioners.